2014
DOI: 10.1364/ao.53.000720
|View full text |Cite
|
Sign up to set email alerts
|

Glucose sensor with a Sagnac interference optical system

Abstract: The angle of optical rotation was measured by detecting the phase difference between clockwise and counterclockwise circular polarized light that propagated in a sensing loop. This polarimeter, or glucose sensor, consisted of a Sagnac interference optical system with a polarization-maintaining optical fiber, so it was not affected by the control limitations of the polarization rotation angle or the optical power fluctuation that occurs with scattered light, reflection, or polarization rotation in an optical sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The manuscript is devoted to solving the first difficulty, which is to realize the measurement of weak optical rotation signals. Many methods have been developed to measure weak optical signals, including the optical heterodyne method [4,5] , Faraday modulation method [6,7] , Sagnac interferometer method [8] , and self-referencing method [9,10] etc.. Among them, the optical system of the self-referencing method is accurate and simple.…”
Section: Introductionmentioning
confidence: 99%
“…The manuscript is devoted to solving the first difficulty, which is to realize the measurement of weak optical rotation signals. Many methods have been developed to measure weak optical signals, including the optical heterodyne method [4,5] , Faraday modulation method [6,7] , Sagnac interferometer method [8] , and self-referencing method [9,10] etc.. Among them, the optical system of the self-referencing method is accurate and simple.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported various forms of glucose sensor using both conventional and crystal fibres. In [24], Binu et al has proposed the fibre optic glucose sensor to sense the RI variation of different glucose concentration (5-25 g) present in the 100 ml distilled water with the experimental demonstration and Tatsuya Kumagai et al [25] has proposed an optical system to sense the glucose of 1 mg/dl resolution for human blood using polarisation maintain principle following the sagnac principle. Further, the sensing mechanism of glucose has been utilised with the help of PCF to produce the high average spectral compact sensitivity where biological liquid of any analyte is infiltrated [26] into any one of micro air hole claddings.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber technology is traditionally used for sensing applications, where a phase shift is measured either in a resonator or through evanescent wave coupling in a tapered fiber. For instance, Sagnac interference in an optical system consisting of a fiber loop with counter-propagating light beams can be used for rotation, temperature, tension, magnetic field sensing [1,2,3] and medical applications [4]. Michelson and Fabry-Perot interferometers are also used for temperature sensing [5,6].…”
Section: Introductionmentioning
confidence: 99%